Code Switching and Code Mixing in Workplace Communication: Implications for Educational Management and Professional Development - Pramisdi Winanto Saputro; Sonya Trikandi; Diardana Prima Sintasari; Ina; Rifaatussalwa Hayati; Aziz Fauzi (Al-Qalam Institue, 2026)
This study aims to describe the forms of code switching and code mixing that occur in workplace communication and to examine their implications from an educational management perspective. A descriptive qualitative approach was employed using observation, listening, audio recording, and documentation techniques. The data consisted of five selected speech events, which revealed two instances of code switching (internal and external) and three instances of code mixing in the form of words, phrases, and clauses. The dominant languages used were Indonesian, Sundanese, Javanese, and English. The findings indicate that code switching and code mixing are influenced by conversational context, speakers’ cultural backgrounds, habitual language use, the presence of a third participant, and the formality of workplace situations. Beyond their linguistic function, these phenomena reflect social interaction patterns, cultural identity, and communication effectiveness in multilingual professional settings. From an educational management perspective, the results highlight the importance of managing language use in workplace learning, communication training, and professional development programs to support effective collaboration and inclusive learning environments.